EXTRACURRICULAR ABACUS TO IMPROVE THE COGNITIVE ARITHMETIC SKILLS OF CHILDREN AGED 5-6 YEARS - Ilyati Zahro, Vanny Rahmayanti Audina; Akhtim Wahyuni (Academic Journal Research, 2024)
Objective: This study evaluates the impact of the abacus extracurricular program on the cognitive development of children aged 5–6 years, focusing on arithmetic skills such as logical thinking, problem-solving, and critical thinking. Methods: A qualitative descriptive method was employed, involving observations, interviews with educators, and documentation analysis at RA Depag 1 Mojokerto. Data were collected from 16 students actively participating in abacus extracurricular activities. Data analysis followed the Miles and Huberman model, encompassing reduction, presentation, and verification to draw conclusions. Results: Findings indicate that abacus activities foster improved arithmetic ability through visual and interactive learning. Children demonstrated increased concentration, memory retention, and fine motor skills via bead manipulation. The weekly group-based learning sessions encouraged collaborative problem-solving and formula memorization within time constraints, effectively stimulating cognitive and motor skill development. Moreover, the integration of abacus learning into extracurricular activities was met with enthusiasm and improved educational outcomes. Novelty: This study highlights the significance of the abacus as a traditional yet effective tool for early cognitive development, emphasizing its dual role in enhancing logical reasoning and fine motor skills. The tailored approach for early learners, focusing on visual and tactile methods, distinguishes this program from conventional math teaching practices.